Kemudahan atau Kehati-hatian? Analisis Penggunaan Layanan Buy Now Pay Later (BNPL) di Kalangan Masyarakat Muslim Indonesia - Sry Lestari; Ismail Pulungan (CV. Ulil Albab Corp, 2026)
The rapid growth of Buy Now Pay Later (BNPL) services has transformed consumer behavior in digital transactions, particularly through Shopee PayLater. This study aims to examine the effects of Perceived Usefulness, Perceived Ease of Use, Trust, Perceived Risk, and Social Influence on users’ Behavioral Intention to use Shopee PayLater, as well as the moderating role of Financial Literacy. This study employed a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Primary data were collected through an online questionnaire distributed to Shopee PayLater users residing in Java Island using purposive sampling. Data were analyzed using SmartPLS 4.0.The results indicate that Trust, Perceived Risk, and Social Influence have positive and significant effects on Behavioral Intention to use Shopee PayLater. In contrast, Perceived Usefulness and Perceived Ease of Use do not significantly influence Behavioral Intention. The moderating effect analysis reveals that Financial Literacy strengthens the relationship between Perceived Usefulness and Behavioral Intention, while weakening the relationships between Perceived Ease of Use, Perceived Risk, and Behavioral Intention. However, Financial Literacy does not significantly moderate the relationships of Trust and Social Influence with Behavioral Intention. These findings suggest that Trust, Social Influence, and financial literacy are important determinants of BNPL adoption. This study contributes to the growing literature on digital financial technology adoption and provides practical implications for BNPL providers in enhancing platform security, transparency, and consumer financial education.